The Enhancement of OSH Training with an Augmented Reality-Based App - Ahmad Alif, Kamal; Syahrul Nizam, Junaini; Abdul Halim, Hashim; Faizal Sufri, Sukor; Muhammad Farez, Said (iJOE, 2021)
Recent advances in training approaches and technology have identified the need to improve training in the field of occupational safety and health (OSH). While many researchers have examined the use of augmented reality (AR) and technology-based classrooms to enhance conventional training practices, quantitative evidence for their effectiveness and motivational impact remains scarce. To contribute to filling this research gap, an AR-based application was developed to enhance OSH training. The enhanced training session was conducted in a closed, safe environment with ten participants with no background in OSH. Pre-test, post-test, and instructional material motivation surveys (IMMS) using a five-point Likert scale were deployed to measure the effectiveness and motivational impact in accordance with the respective ARCS factors. The empirical results obtained show that participants performed significantly better in the post-tests than in the pre-tests (mean = 14.60, s = 1.71, t(9) = –12.11 with p-value < 0.001). The IMMS results show that the perceived motivation arising from the AR-based application resulted in the highest mean score for the satisfaction factor (4.80) followed by the relevance (4.65), confidence (4.60), and attention (4.55) factors. The results of the evaluation suggest that the AR-based application boosted participants’ active learning behavior, engagement, and interest during the enhanced training session and produced a better learning outcome and experience.